Coral Larvae Move toward Reef Sounds - Vermeij, Mark J. A.; Marhaver, Kristen L.; Huijbers, Chantal M.; Nagelkerken, Ivan; Simpson, Stephen D. (PLOS ONE, 2010)
Free-swimming larvae of tropical corals go through a critical life-phase when they return from the open ocean to select a suitable settlement substrate. During the planktonic phase of their life cycle, the behaviours of small coral larvae (<1 mm) that influence settlement success are difficult to observe in situ and are therefore largely unknown. Here, we show that coral larvae respond to acoustic cues that may facilitate detection of habitat from large distances and from upcurrent of preferred settlement locations. Using in situ choice chambers, we found that settling coral larvae were attracted to reef sounds, produced mainly by fish and crustaceans, which we broadcast underwater using loudspeakers. Our discovery that coral larvae can detect and respond to sound is the first description of an auditory response in the invertebrate phylum Cnidaria, which includes jellyfish, anemones, and hydroids as well as corals. If, like settlement-stage reef fish and crustaceans, coral larvae use reef noise as a cue for orientation, the alleviation of noise pollution in the marine environment may gain further urgency.